Effect of powders on microstructure and performance of inconel 718 alloy prepared by SPS - Qinggong, Jia; Qingxiang, Wang; Shuhua, Liang (Materials research express, 2022)
In this paper, 15–53 μ m spherical powders obtained by plasma rotating electrode (PREP) and argon atomization (VIGA) were used to prepare the Inconel 718 alloy through spark plasma sintering(SPS), and then the sintered alloy was treated by solid solution and aging heat treatment. The effect of different powders on the microstructure and properties of Inconel 718 alloy as sintered and heat treated was studied. The results show that high density Inconel 718 alloy can be obtained by SPS technology, and the original particle boundary of powder can be reduced, and the original particle boundary of PREP is less. According to the densification process of spherical powder during SPS process, the change law of powder microstructure in rapid sintering is established.